Birds of Teal Lake in Little Andaman Island - Tilak, A. C. (Indian Forester, 2014)
The study was conducted in Teal Lake from July 2012 to March 2013 in Little Andaman Island. To study water and associate birds that visits this wetland. A total of 28 birds were recorded during the study period. Lesser whistling teal, Indian purple moorhen and common moorhen were recorded with 80, 24 and 16 individuals. Only 1 individual of Andaman teal was recorded once from the lake. Great egret and little egret were common visitors of the lake. Other birds recorded were Common coots, Indian pond heron, Andaman white breasted water hen, Andaman white collared kingfisher, Andaman white breasted kingfisher, Chestnut bittern, Little stint, common sandpiper, white breasted wood swallow, black winged stilt , pheasant tailed jacana, red wattled lapwing, purple heron etc.